Alienation in the Plastic Arts: Ceramics as a Model - Al-Basha, Narmin Ramzi Qasim Mustafa; Al-Badran, Oras Jabbar Suhaim (South Asian Journal of Social Sciences and Humanities, 2023)
The current research is concerned with studying (alienation in the plastic arts (ceramics as a  model), as alienation was studied in terms of its effect on the artist, which in turn had its  effect on the artistic work in formation, to be spatial discrepancies and displacements whose  vocabulary is mixed with oppositions, disruption, and displacement, which create an apparent  formal defect according to the contemporary perspective, with The development of  technology and technique. Alienation appeared to be found in form in the plastic arts in  general, and one of these arts is ceramics. Alienation in ceramics broke the traditional pattern  and transcended the vocabulary of work associated with intellectual and conceptual  transformations that resulted in the elements of alienation, including the art schools that  brought about a shift in the artist’s concepts toward rejection. Everything that is familiar and  traditional, as the artist sought to search for the idea that is different from the concept through  the influence of the potter, which was achieved as a result of communication between art and  society, which gives renewed concepts to the idea to achieve alienation according to the  transformations of ceramic art, and the idea from which the potter started and developed  treatments for reality through research was adopted.
Keywords: Alienation; plastic arts; ceramics